1989
DOI: 10.1111/j.1439-037x.1989.tb00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drought Conditions at Boiling Stage on Some Chemical Constituents of Cotton Plant

Abstract: The investigation was carried out to study the effect of drought conditions at boiling stage on chloroplast pigments and anthocyanin, in leaves, carbohydrate, phenols and total amino nitrogen content in leaves and roots, oil and protein contents in bolls of different ages. Seeds of cv. Giza 75 cotton were sown during 1987 and 1988 seasons in pots of 30 cm in diameter containing 11 kg of soil; after complete germination, thinning was carried out leaving one plant per pot. Plants were subjected to water stress c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…Proline would be a good source of energy and N for the plant under drought conditions. These results are agreement with the findings of Ahmed et al (1989), Namich (1997) and Ashraf and Foolad (2007). Natural materials significantly affected leaf total chlorophyll, phenols and proline content at 114 days after planting, in favor of spraying potassium citrate and significantly affected leaf carotenoids content, in favor of spraying salsalic acid.…”
Section: I-leaf Chemical Compositionsupporting
confidence: 92%
“…Proline would be a good source of energy and N for the plant under drought conditions. These results are agreement with the findings of Ahmed et al (1989), Namich (1997) and Ashraf and Foolad (2007). Natural materials significantly affected leaf total chlorophyll, phenols and proline content at 114 days after planting, in favor of spraying potassium citrate and significantly affected leaf carotenoids content, in favor of spraying salsalic acid.…”
Section: I-leaf Chemical Compositionsupporting
confidence: 92%
“…In our experiments, HPLC-separated basic polyphenol species, namely cinnamic acid derivatives (chlorogenic acid isomers) and flavonoids (mainly quercetin glycosides) were shown to decline in the drought-subjected plants ( Table 1). Decline of total leaf polyphenols has also been observed in pot trials with drought-experiencing cotton (Ahmed et al 1989). However, the fact that despite drought conditions the tolerant cv.…”
Section: Discussionmentioning
confidence: 85%
“…We observed that in the maize cultivars, total phenolics increased under drought stress. In contrast to these findings, drought stress reduced phenolics in cotton (Ahmad et al, 2008), canola (Shafiq et al, 2014), corn (Ali et al, 2011), while in contrast, an increase was observed in carrot (Razzaq et al, 2017) plants under stress conditions. In a previous study, an increase in AsA was observed in canola (Shafiq et al, 2014) plants that is analogous to what was observed in the present study under water deficit conditions.…”
Section: Discussionmentioning
confidence: 89%